Dampak Kebijakan Jaminan Kesehatan Nasional terhadap Efisiensi Rumah Sakit: Studi Kasus di Provinsi Sulawesi Selatan - Irwandy Irwandy; Amal Chalik Sjaaf (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Managing the hospital efficiency with still control the hospital quality and cost is a key to survive in NationalHealth Insurance Era. The objective of this study was to determine the impact of the implementation of theNational Health Insurance Policy (NHI) on the efficiency level of Hospital in South Sulawesi Province, Indonesia.The level of efficiency was analyzed using the Data Envelopment Analysis method. The study population was allBLUD hospitals in South Sulawesi Province. The Samples of research were 25 hospitals. Data from years 2014 to2017 are used to analyze. The results showed, in average the hospitals achive the efficiency level only in year 2016.In years 2014, 2015 and 2017 the hospitals were not efficient. The changing in the healthcare system, especially onpayment system to hospitals in JKN era, have had a negative impact on the level of hospital efficiency because theunadequate INA CBGs Tariff and hospital claims payment disrupted. Therefore, the government needs to overcomethose problems.